A Reinterpretation of Chiu Keng Guan’s Ola Bola: a Redefined Notion of Bangsa Malaysia from an Islamic Perspective - Ayob, Abdul Halim; Yosri, Ali Abdul Rahman (UUM PRESS, 2024)
National identity plays a crucial role in the development of a nation, with its essence continually evolving over time. Consequently, various endeavors have been made by authorities to shape a national identity in Malaysia. Among these efforts is Mahathir's concept of Bangsa Malaysia. Despite being labeled as a nonIslamic production, Chiu Keng Guan's film, Ola Bola, subtly reflects Islamic principles in fostering national identity. This study aims to redefine the emergence of a Malaysian national identity depicted in Ola Bola, aligning with Islamic values, and to challenge the established notion of Bangsa Malaysia. Through a thematic analysis and literature review of Ola Bola, the film's narrative is revisited and examined. Ola Bola, effectively conveying Islamic values in nurturing a cohesive national identity, was directed by a non-Muslim Malaysian, reshaping the predominantly Malay-centric concept of Bangsa Malaysia, as is evident. The film's three principal themes which are equality and fairness,the spirit of brotherhood and a shared identity and common goals, redefine Bangsa Malaysia and resonate with Islamic ideals of multiculturalism and a pluralistic society within the Malaysian context